2013
DOI: 10.1007/s10103-013-1377-3
|View full text |Cite
|
Sign up to set email alerts
|

What is the best treatment to decrease pro-inflammatory cytokine release in acute skeletal muscle injury induced by trauma in rats: low-level laser therapy, diclofenac, or cryotherapy?

Abstract: Currently, treatment of muscle injuries represents a challenge in clinical practice. In acute phase, the most employed therapies are cryotherapy and nonsteroidal anti-inflammatory drugs. In the last years, low-level laser therapy (LLLT) has becoming a promising therapeutic agent; however, its effects are not fully known. The aim of this study was to analyze the effects of sodium diclofenac (topical application), cryotherapy, and LLLT on pro-inflammatory cytokine levels after a controlled model of muscle injury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 25 publications
0
27
0
2
Order By: Relevance
“…The positive effects of LLLT on the muscle repair process after different types of injury are well established in the literature and include an improvement in collagen remodeling, modulation of the gene expression of myogenic regulatory factors, increases in the number of immature fibers and angiogenesis and a reduction in the tissue concentration of pro‐inflammatory cytokines . However, varied effects are achieved depending on the administration parameters, such as enhanced functioning , improvements in range of motion , the attenuation of dysesthesia and modulation of the concentration of inflammatory cytokines .…”
Section: Discussionmentioning
confidence: 99%
“…The positive effects of LLLT on the muscle repair process after different types of injury are well established in the literature and include an improvement in collagen remodeling, modulation of the gene expression of myogenic regulatory factors, increases in the number of immature fibers and angiogenesis and a reduction in the tissue concentration of pro‐inflammatory cytokines . However, varied effects are achieved depending on the administration parameters, such as enhanced functioning , improvements in range of motion , the attenuation of dysesthesia and modulation of the concentration of inflammatory cytokines .…”
Section: Discussionmentioning
confidence: 99%
“…In animal models, photobiomodulation has been found to reduce the expression of TNF-α [17,41,42], IL-1β [15,41,42], IL-6 [41,42], COX-2 [43,44], iNOS [45,46] and NFκβ [45]. As macrophages are the key cells in the muscle repair process, the results presented herein suggest that the in vivo effects of photobiomodulation may be largely dependent on these cells and could indicate new therapeutic possibilities, not only for muscle injuries [18].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that low-level laser therapy (LLLT) has analgesic effects [11][12][13], modulates the levels of inflammatory mediators, and has anti-inflammatory effects [14][15][16]. Furthermore, recent animal studies [17][18][19] and human studies [10,20,21] have hinted at the possibility of LLLT in lowering the levels of CK, other muscle damage markers, and oxidative stress after exercise.…”
Section: Introductionmentioning
confidence: 96%